Tuning tuft cells: new ligands and effector functions reveal tissue-specific function. (February 2021) - Billipp, Tyler E; Nadjsombati, Marija S; von Moltke, Jakob
Highlights: Tuft cells reside in the epithelium of airway, intestinal, and urogenital tissues. Tuft cell receptors and effector functions are tuned in a tissue-specific manner. Tuft cells detect noxious substances and ligands from bacteria, helminths, or protists. Tuft cells modulate immune responses and neurologic function. Tools to identify and study human tuft cells are improving. Abstract : Tuft cells are rare chemosensory epithelial cells that monitor their environment and relay messages to the surrounding tissue via secretion of neuromodulatory and immunomodulatory molecules. In the small intestine tuft cells detect helminth infection, protist colonization, and bacterial dysbiosis, and initiate a type 2 immune response characterized by tissue remodeling. In the airways, tuft cells sense bacteria, allergens, and noxious stimuli and drive evasive behavior, neuroinflammation, and anti-bacterial responses. Here we summarize the most recent tuft cell research and discuss how these findings have provided insight into tuft cell diversity. Built around a core program of chemosensing, tuft cell receptors and effector functions are tuned to the unique environmental exposure and physiology of their surrounding tissue.